Elles@centrepompidou: artistes femmes dans la collection du Musée national d'art moderne, Centre de création industrielle. - Musée national d'art moderne/Centre de création industrielle (France); Centre Georges Pompidou.; Morineau, Camille; Centre Georges Pompidou. (Centre Pompidou, 2009)
Le Centre Pompidou met à l'honneur près de 200 artistes femmes : vidéastes, peintres, sculpteurs, etc., et plus de 500 de leurs oeuvres montrant ainsi la conquête par les femmes du statut d'artiste au cours du XXe siècle. Avec une chronologie mettant en parallèle les créations ou actions des femmes artistes et des faits de société.
Keywords: 1900-1999; 2000 à aujourd'hui; arts; arts visuels et médiatiques; cours; discipline; exposition; femmes* artistes; har4600; premier cycle; périodes historiques

« Un studio à soi ». Entrevue avec Bérengère Marin Dubuard, du Studio XX - Parent, Sylvie (ETC, 2008)
https://id.erudit.org/iderudit/34774ac
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; arts; arts visuels et médiatiques; cyberféminisme; discipline; environnement; femmes* artistes; organisations féministes; périodes historiques; québec; ressource en ligne; régions géographiques; technologie; thématiques; travail

WACK!: art and the feminist revolution - Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif); Butler, Cornelia H.; Mark, Lisa Gabrielle; Museum of Contemporary Art (Los Angeles, Calif) (Museum of Contemporary Art, 2007)
Groundbreaking art from a revolutionary era, featuring work by more than 120 international artists, from Louise Bourgeois and Yoko Ono to Martha Rosler, Marina Abramović, and Cindy Sherman. There had never been art like the art produced by women artists in the 1970s, and there has never been a book with the ambition and scope of this one about that groundbreaking era. WACK! documents and illustrates the impact of the feminist revolution on art made between 1965 and 1980, featuring pioneering and influential works by artists who came of age during that period, Chantal Akerman, Lynda Benglis, Theresa Hak Kyung Cha, Valie Export, Mary Heilmann, Sanja Iveković, Ana Mendieta, Annette Messager, and others, as well as important works made in those years by artists whose careers were already well established, including Louise Bourgeois, Judy Chicago, Sheila Levrant de Bretteville, Lucy Lippard, Alice Neel, and Yoko Ono. The art surveyed in WACK! includes work by more than 120 artists, in all media, from painting and sculpture to photography, film, installation, and video, arranged not by chronology but by theme: Abstraction, "Autophotography," Body as Medium, Family Stories, Gender Performance, Knowledge as Power, Making Art History, and others. WACK!, which accompanies the first international museum exhibition to showcase feminist art from this revolutionary era, contains more than 400 color images. Highlights include the figurative paintings of Joan Semmel; the performance and film collaborations of Sally Potter and Rose English; the untitled film stills of Cindy Sherman; and the large-scale, craft-based sculptures of Magdalena Abakanowicz. Written entries on each artist offer key biographical and descriptive information and accompanying essays by leading critics, art historians, and scholars offer new perspectives on feminist art practice. The topics, including the relationship between American and European feminism, feminism and New York abstraction, and mapping a global feminism, provide a broad social context for the artworks themselves. WACK! is both a definitive visual record and a long-awaited history of one of the most important artistic movements of the twentieth century. Essays by: Cornelia Butler, Judith Russi Kirshner, Catherine Lord, Marsha Meskimmon, Richard Meyer, Helen Molesworth, Peggy Phelan, Nelly Richard, Valerie Smith, Abigail Solomon-Godeau, Jenni Sorkin Artists include: Marina Abramović, Chantal Akerman, Lynda Benglis, Dara Birnbaum, Louise Bourgeois, Judy Chicago, Lygia Clark, Jay DeFeo, Mary Beth Edelson, Valie Export, Barbara Hammer, Susan Hiller, Joan Jonas, Mary Kelly, Maria Lassnig, Linda Montano, Alice Neel, Senga Nengudi, Lorraine O'Grady, Pauline Oliveros, Yoko Ono, Orlan, Howardena Pindell, Yvonne Rainer, Faith Ringgold, Ketty La Rocca, Ulrike Rosenbach, Martha Rosler, Betye Saar, Miriam Schapiro, Carolee Schneemann, Cindy Sherman, Hannah Wilke
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire et politique; premier cycle; périodes historiques; thématiques

Global feminisms: new directions in contemporary art - Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center.; Reilly, Maura; Nochlin, Linda; Brooklyn Museum.; Davis Museum and Cultural Center. (Merrell ;, 2007)
Catalogue for the exhibition Global Feminisms, that took place at the Brooklyn Museum in 2007. The first international exhibition exclusively dedicated to feminist art from 1990 to the present. The show consists of work by approximately eighty women artists from around the world and includes work in all media—painting, sculpture, photography, film, video, installation, and performance. Its goal is not only to showcase a large sampling of contemporary feminist art from a global perspective but also to move beyond the specifically Western brand of feminism that has been perceived as the dominant voice of feminist and artistic practice since the early 1970s.This exhibition is arranged thematically and features the work of important emerging and mid-career artists.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; intersectionnalité; premier cycle; périodes historiques; thématiques

Body art and performance: the body as language - Vergine, Lea; Vergine, Lea (Skira, 2007)
When The Body as Language ("Body-art" and Performance) appeared in 1974, it was immediately a huge publishing hit, reviewed by some of the most influential art historians and writers (Giulio C. Argan, Edoardo Sanguineti, Max Kozloff, Lucy Lippard, François Pluchart, Peter Gorsen, Evelyn Weiss and many others). A direct testimony of the birth and development of one of the most controversial art trends, Lea Vergine's book avails of a series of texts by the artists themselves, whom the author had asked to contribute with a statement about the illustrations of their work. Featuring a thorough documentation of original photographs and film photograms, videotapes, happenings, actions and performances, the book analyses the evolution of this phenomenon through the works of sixty artists, including Gina Pane, Gilbert & George, Urs Lüthi and Katharina Sieverding, Rebecca Horn, Trisha Brown, Günter Brus and many others who have worked with and on the body. In an absolutely unusual publishing event, nearly thirty years after the first edition, the text–by now a classic–is republished with all the original photographic material. The volume is enhanced and brought up-to-date by an afterword by Lea Vergine, who observes the changes of Body Art throughout the nineties: Orlan, Stelarc, Ron Athey, Franko B., Yasumasa Morimura, Jana Sterbak, Matthew Barney are "virtuosos of disorder and hungry for afflictions of any and every kind, mystics–like persons who display the subjection of their bodies to cruel and invasive devices, or who revel in virtual fantasies of such self-inflicted pains–destroy themselves in order newly to find themselves. . . . They finally pay a visit to the world of the saints and victims, exploring and prolonging its seductions.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; femmes* artistes; har4600; histoire de l'art; performance; premier cycle; thématiques

Self image: technology, representation, and the contemporary subject - Jones, Amelia (Routledge, 2006)
"Self/Image explores the ways in which contemporary artists have deployed new technologies of representation, from analogue photography to more recent artistic practices including digital imaging, performance, robotics, film and video installations, to explore and articulate shifting modes of subjectivity. This book is one of the first full-length studies to investigate the complex intersubjective relations among these diverse artistic practices." "Including over 100 illustrations from mainstream film to independent film, video art, performance and the visual arts, this important and original book provides an excellent companion to more general studies of contemporary art history, and media and cultural studies in the post-1960 period."–Résumé de l'éditeur.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; film; har4600; histoire de l'art; performance; portrait; premier cycle; périodes historiques; représentation; thématiques; théorie de l'art

Féminin pluriel et féminismes en arts visuels au Québec - Boileau, Julia (Esse, 2004)
Il y a plus de 20 ans, en tant qu’historienne de l’art, j’avais posé la question à savoir si l’apport des femmes en art contemporain allait changer quelque chose à la pratique artistique et comment, de même qu’à la pratique de la critique et de l’histoire de l’art1. Ce qui suit est une évocation des principaux questionnements que l’art des femmes et les féminismes en art ont amenés au sein de l’art contemporain. La pratique de l’art mais aussi les pratiques muséologiques ont-elles été affectées par l’arrivée en nombre des femmes sur la scène de l’art moderne et contemporain ? La question des femmes recèle-t-elle encore une pertinence dans le monde de l’art contemporain d’aujourd’hui ?
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; art contemporain; arts; arts visuels et médiatiques; canada; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques

X-elles: le sexe par les femmes - Millet, Catherine..; Leydier, Richard 19.... (Art Press, 2004)
"Adresses Internet p. 112-113."Contient : Editorial : un raz de marée, par Catherine Millet et Richard Leydier, p. 5-7. Chapitre 1 : Elles débarquent! : L'acte pour l'art, par Louis-José Lestocart, p. 10-14 ; Bandes de femmes, par Bernard Joubert, p. 15-21 ; Éros féminin surréel, par Victoria Combalía, p. 22-27 ; Ellen von Unwerth. Naughty Girls!, interview par Richard Leydier, p. 28-31 ; Organes et orgasmes. Sur quelques chanteuses sexy, par Stéphane Pencréac'h, Stéphane Ruiz et Richard Leydier, p. 32-36; Dans le train fantôme de Catherine Breillat, témoignages recueillis par Brigitte Ollier, p. 37-40 ; Clarisse Hahn. La sexualité dans le tissu de la vie, interview par Catherine Millet et Louis-José Lestocart, p. 41-44 ; Portfolio #1 : Aude du Pasquier-Grall, Sonia Koumskoff-Raissi, Nicole Tran Ba Vang, Ornela Vorpsi, Friedl Kubelka, Anne Dion., p. 45-50. Chapitre 2 : Un autre porno : Angela, Loulou et les autres ... Quand les femmes prennent la caméra, par Stéphane Ruiz, p. 52-60 ; Monika Treut. Female Misbehavior, par Thibaut de Ruyter, p. 61-65 ; Maria Beatty. De la surface à la profondeur, par Catherine Corringer, p. 66-70 ; Shu Lea Cheang. Un genre en soi, Interview par Louis-José Lestocart, p. 71-74 ; Il y a une vie après le X : Brigitte, Tabatha, Ilona et Traci, par Laurent Goumarre, p. 75-80 ; Ovidie, plus librement, interview par Laurent Goumarre, p. 81-84 ; Portfolio #2 : Kiki Seror, Virginie Boursette, Béatrice Cussol, Bettina Rheims, Pascale Lafay, Diana Michener, p. 85-90. Chapitre 3 : Autoportraits : Lamia Ziadé. "Je suis une vraie petite femme d'intérieur", interview par Brigitte Ollier, p. 92-96 ; Chloë des Lysses. Une femme en danger, interview par Richard Leydier, p. 97-101 ; Madeleine Berkhemer. Élastique, érotique, par Alix Rozès, p. 102-105 ; Elke Krystufek. Le miroir qui met à nu, interview par Joerg Bader, p. 106-109 ; La pornographie, to remember, par Judith Brouste, p. 110-111 ; Les femmes sur le Web, par Chloë des Lysses, p. 112-113.
Keywords: 2000 à aujourd'hui; 2000-2009; arts; arts visuels et médiatiques; corps; cours; discipline; europe; france; har4600; histoire de l'art; premier cycle; périodes historiques; régions géographiques; sexualité; thématiques

The art of history African American women artists engage the past - Collins, Lisa Gail (Rutgers University., 2002)
In this lively and engaging book, Lisa Gail Collins examines the work of contemporary African American women artists. Her study comes at a time when an unprecedented number of these artists-photographers, filmmakers, painters, installation and mixed-media artists-have garnered the attention and imagination of the art-viewing public. To better understand the significance of this particular historical moment in American visual arts, Collins focuses on four "problems" that recur when these artists confront their histories: the documentation of truth; the status of the black female body; the relationship between art and cultural contact and change; and the relationship between art and black girlhood. By examining the social and cultural histories which African American women artists engage, Collins illuminates a dialogue between past and present imagemakers. The Art of History is a major contribution to the study of American visual culture. It will be of use to both scholars and students in art history, African American studies, American studies, and women's studies.
Keywords: afro-féminisme; amériques; approches et analyses; arts visuels et médiatiques; corps; cours; discipline; fem1000; femmes* afro-américaines; féminisme afroaméricain; féminismes noirs; pratiques féministes; premier cycle; régions géographiques; thématiques; états-unis

Art and feminism - Reckitt, Helena; Phelan, Peggy (Phaïdon, 2001)
Le féminisme a eu un impact crucial sur l'art de la fin du XXe siècle, inspirant certains des développements les plus pionniers de la sculpture, de la peinture, de la performance, de la photographie, du cinéma et de l'installation. Le monde de l'art a été transformé par les féministes qui en même temps ont été parmi ses principaux critiques. Le féminisme a redéfini les termes mêmes de l'art de la fin du XXe siècle : il a exposé des hypothèses sur le genre ; il a politisé le lien entre privé et public ; il a souligné la spécificité de l'art marqué par le sexe, la race, l'âge et la classe. Sélectionnée par l'éditrice et chercheuse Helena Reckitt, cette collection présente la riche diversité de l'art influencé par le féminisme des années 1960 au début du XXIe siècle. Pas seulement une histoire complète, le livre juxtapose des œuvres de nombreuses artistes qui ne sont généralement pas montrées ou discutées ensemble, ouvrant de nouvelles connexions entre les personnalités clés. Peggy Phelan, parmi les théoriciennes féministes contemporaines les plus connues, parcourt l'histoire de l'art féministe, ouvrant de nouvelles perspectives sur le travail d'artistes allant de Georgia O'Keeffe et Louise Bourgeois à Cindy Sherman et Pipilotti Rist. Les documents comprennent les principaux textes critiques de chaque période, allant des écrits de Simone de Beauvoir à la critique d'art pionnière de Lucy R Lippard, en passant par les contributions féministes de Craig Owens à la critique postmoderne, ainsi que de nombreuses artistes importantes.
Keywords: 1900-1999; 2000 à aujourd'hui; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; fem1000; histoire de l'art; interdisciplinarité; pratiques féministes; premier cycle; périodes historiques; théories féministes

Amazons of the avant-garde: Alexandra Exter ... [et al.] - Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin.; Bowlt, John E.; Drutt, Matthew; Deutsche Guggenheim Berlin. (Solomon R. Guggenheim Museum, 2000)
Amazons of the Avant-Garde presents work by six Russian women who contributed to the development of modern art in the first quarter of the 20th century: Alexandra Exter, Natalia Goncharova, Liubov Popova, Olga Rozanova, Varvara Stepanova, and Nadezhda Udaltsova. The catalogue includes several essays that discuss the hindrances and influences affecting women in Russian avant-garde art circles. In addition, each artist featured in the exhibition is individually discussed at length, along with biographical timelines and excerpts of their writings from letters and publications. Color reproductions of the works in the exhibition accompany the essays to form a cohesive illustration of the art world in Russia during the first decades of the 20th century and the women who changed the aesthetic canons of their time. Alexandra Exter – Natalia Goncharova – Liubov Popova – Olga Rozanova – Varvara Stepanova – Nadezhda Udaltsova
Keywords: 1900-1999; 1910-1919; 1920-1929; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; premier cycle; périodes historiques; russie; régions géographiques; thématiques

Femmes & art au XXe siècle: le temps des défis - Dumas, Marie-Hélène (Lunes, 2000)
Que cela soit dans les plus prestigieuses expositions ou bien dans les livres consacrés à l'art, le très faible nombre de femmes représentées ou citées - en tous les cas en France - laisse perplexe. Pourtant, les femmes ont toutes les qualités pour être reconnues comme de grands artistés. Le débat autour du statut de la <> demeure donc plus que jamais d'actualité. Cet ouvrage pose la question de la reconnaissance des femmes dans le milieu artistique tout au long du XXe siècle. Par une mise en perspective historique - car l'art n'est pas en dehors de la société - il analyse comment les femmes ont participé à la création et au développement de différents mouvements (constructivisme, dadaïsme, surréalisme, art féministe. Fluxus, ou encore le cyber-art). Il permet également de mieux comprendre les démarches d'un grand nombre d'artistes, certaines très connues comme ou Yoko Ono ou Sophie Calle, ou ne devant surtout pas être oubliées comme Hannah Höch, ou Natalia Gontcharova. Ce livre vous invite à découvrir la richesse créatrice dont ont témoigné de nombreuses femmes de tous pays tout au long du XXe siècle, mais qui demeure trop souvent invisible.
Le texte suivant : Collin, Françoise. (2000). La sortie de l’innocence, 175-189 a été donné en lecture au cours HAR4600.
Keywords: 1900-1999; arts; arts visuels et médiatiques; cours; discipline; femmes* artistes; har4600; histoire; histoire de l'art; histoire et politique; premier cycle; périodes historiques; sciences humaines; sex1911; thématiques

L'art des femmes - Institut de recherches et d'études féministes (FéminÉtudes, 2000)
Cette publication du début du millénaire porte sur les femmes artistes. *** FéminÉtudes est une revue étudiante, féministe et multidisciplinaire. La revue est née en 1995 de l’initiative d’étudiantes féministes dans l’intérêt de partager leurs recherches et de créer un groupe affinitaire. La revue est dirigée par des collectifs de rédaction bénévoles et autogérés, et soutenue par l’Institut de Recherches en Études Féministes (IREF) de l’Université du Québec à Montréal. Au fil des ans, FéminÉtudes a réussi à se bâtir une réputation et une légitimité dans le champ de la recherche en études féministes, tout en offrant une tribune au travaux et aux réflexions de dizaines d’étudiant.e.s. Au-delà de la recherche, c’est également pour l’avancement des luttes féministes que FéminÉtudes souhaite continuer à grandir.
Discipline en libre accès : https://iref.uqam.ca/feminetudes/vol-5-no-1-2000-femmes-artistes/
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; arts; arts visuels et médiatiques; discipline; féminétudes; histoire de l'art; histoire et politique; militance; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; écriture des femmes*; études littéraires